2010
DOI: 10.1021/jp1062463
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polypyrrole/Tungsten Oxide Metacomposites with Negative Permittivity

Abstract: Polypyrrole (PPy) nanocomposites reinforced with tungsten oxide (WO 3 ) nanoparticles (NPs) and nanorods (NRs) are fabricated by a surface-initiated polymerization method. The electrical conductivity is observed to depend strongly on the particle loadings, molar ratio of oxidant to pyrrole monomer, and the filler morphology. The electron transportation in the nanocomposites follows a quasi-three-dimensional variable range hopping (VRH) conduction mechanism as evidenced by the temperature-dependent conductivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
125
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 185 publications
(133 citation statements)
references
References 66 publications
(104 reference statements)
8
125
0
Order By: Relevance
“…In a nonexhaustive list, one can remind that polypyrrole/WO 3 nanomaterials based composite materials possess a rare negative permittivity and their switching frequency can be tuned with the help of particle loading. In particular, among other parameters, increased nanoparticle loading was also shown to improve the electrical conductivity, dielectric permittivity, and thermal stability of the resulting nanocomposites [7]. One should also notice that magnetite incorporation stabilizes the polaronic form of polypyrrole matrices and also preserves it from further oxidation [8] or allows production of unexpected 1 µm wide stripe-like microstructures resulting from the self-assembly of magnetic components [9].…”
Section: Introductionmentioning
confidence: 92%
“…In a nonexhaustive list, one can remind that polypyrrole/WO 3 nanomaterials based composite materials possess a rare negative permittivity and their switching frequency can be tuned with the help of particle loading. In particular, among other parameters, increased nanoparticle loading was also shown to improve the electrical conductivity, dielectric permittivity, and thermal stability of the resulting nanocomposites [7]. One should also notice that magnetite incorporation stabilizes the polaronic form of polypyrrole matrices and also preserves it from further oxidation [8] or allows production of unexpected 1 µm wide stripe-like microstructures resulting from the self-assembly of magnetic components [9].…”
Section: Introductionmentioning
confidence: 92%
“…Looking into various reports [20][21][22][23][24][25][26][27][28] on materials done earlier, the underneath science was understood. Similar system, such as of PVDF/MWCNT has been studied by G.S.…”
Section: Aip Advances 6 065107 (2016)mentioning
confidence: 99%
“…[18][19][20][21] Change in ε ′ (and further Tan δ) from positive to negative after percolation threshold is due to induction polarization. [23][24][25][26][27] To further evaluate the SE data for all samples and to check whether the high SE is due to reflection and /or absorption, the raw data was again looked into. It was found that, with the incorporation of various wt% of MWCNT in the PVDF, the absorption parameter increased concomitantly in the 5 wt% sample and above, as compared to the reflection contribution.…”
Section: Aip Advances 6 065107 (2016)mentioning
confidence: 99%
“…Polymer nanocomposites (PNCs) based on conjugated polymers (CPs) including polythiophene [1,2] polypyrrole (PPy) [3,4], poly(DNTD) [5,7], polyaniline (PANI) [8,9] and their derivatives have attracted huge attention. The methodology for combining CPs and inorganic materials has announced PANI because of its fascinating properties such as facile polymerization in aqueous media [10][11][12][13] or nonaqueous media [14], versatile redox behavior, good stability in air, low cost, high conductivity and high pseudocapacitance [15,16].…”
Section: Introductionmentioning
confidence: 99%